Atherosclerotic carotid plaque segmentation - Loizou, Christos P.; Pattichis, Constantinos S.; Istepanian, Robert S H; Pantziaris, Marios; Nicolaides, Andrew N. (My University, 2004)
Atherosclerosis is the major cause of heart attack and stroke in the western world. In this paper we present a computerized method for segmenting the athrerosclerotic carotid plaque from ultrasound images. The method uses the blood flow image first to detect the initial contour of the plaque, and then despeckle filtering and snakes to deform the initial contour for best fit of plaque boundaries. The accuracy and reproducibility of this method was tested using 35 longitudinal ultrasound images of carotid arteries and the results were compared with the manual delineations of an expert. The comparison showed that the computerized method gives satisfactory results with no manual correction needed in most of the cases. The true positive fraction, TPF, true negative fraction, TNF, false negative fraction, FNF and false positive fraction, FPF, were 86.44%, 84.03%, 8.5%, and 7% respectively.
Keywords: Carotid plaque; Segmentation; Snakes